Long‐term survival in a dog with probable thyroid storm - Jeffrey Beverly; Armi Pigott; Claire E. Puzio; Meghan Rivera (Clinical Case Reports, 2023)
Key Clinical Message Thyroid storm is a rare, life‐threatening endocrine emergency that may occur in dogs. With rapid identification and early aggressive therapy, long‐term survival is possible. Abstract The aim of this paper was to describe the successful emergency management and long‐term survival of a dog with probable thyroid storm. We present proposed guidelines for the characterization of thyroid storm in dogs, and treatment considerations as utilized for this patient. A 6‐year‐old female spayed German Shepherd Dog was presented to a multispecialty center for radiation planning and treatment of a previously diagnosed nonresectable functional thyroid carcinoma. Recovering from anesthesia, the patient developed clinical features that would qualify as thyroid storm using human metrics. The patient improved with aggressive treatment of thyroid storm, extrapolating from human and feline recommendations. This is the first known report of long‐term survival in a canine with suspected thyroid storm. The crisis was effectively identified and emergently treated.